Transurethral neoorifice (TUNO) for ectopic obstructive megaureter with preserved function in infants - A. Parente; V Vargas; A Escassi; JM Angulo; RM Paredes (Journal of Pediatric Surgery Open, 2023)
Aim: To present the creation of a transurethral neoorifice (TUNO) near the trigone as an initial approach in duplicated ectopic megaureters with preserved moiety function to avoid external urinary diversion. Methods: We have treated with these technique 4 infants. They presented unilateral duplicated system and ectopic obstructive upper ureter. All patients were symptomatic with at least two urinary infections despite nocturnal antibiotic prophylaxis. Scintigraphy showed a 29±11% moiety partial function. In all cases the urethrocystoscopy failed to show the orifice of the ectopic ureter. Under ultrasound scan and direct cystoscopic vision the retrovesical ectopic ureter was punctured transvesically. The puncture was done with a 4Fr needle and contrast was instilled in the ectopic ureter to perform retrograde pyelogram. Through the puncture needle a 0,014´´guidewire was inserted into the upper moiety. The punctured site was then dilated with a high-pressure balloon and the neomeatus edge was coagulated with monopolar electrocautery to achieve cohesion. Results: Mean operative time was 62 ± 10 min. The mean age at treatment was 6.8 ± 2.9 months. There were not perioperative or postoperative complications. Urinary tract infections disappeared in all cases. The assessment done 3 months postoperatively demonstrated a significant decrease in the grade of the hydronephrosis and retrovesical ureter diameter (4 mm vs 20 mm). Moiety function improved in 2 cases. Conclusion: Creation of TUNO is a minimally invasive technique successful as the initial management of ectopic ureter. In our experience, it could avoid urinary tract infections, decreases ureteral dilatation and preserves parenchyma function.